L q regularisation‐based synthetic aperture radar image feature enhancement via iterative thresholding algorithm - Bi, Hui; Zhang, Bingchen; Wang, Zhengdao; Hong, Wen (Electronics letters, 2016)
A novel L q (0 < q ≤ 1) regularisation‐based synthetic aperture radar (SAR) image feature enhancement method via SAR complex image data is presented. Compared with conventional L q regularisation‐based compressive sensing imaging technique with full‐sampling raw data, the proposed method can achieve the same effect of image feature enhancement while enjoying much less computational cost. Through simulations and experiments, the superiority of the proposed method is demonstrated in terms of sidelobe, azimuth ambiguity, clutter suppression and super‐resolution.